2020
DOI: 10.13189/ujer.2020.082006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Willingness to Communicate in English and Classroom Environment

Abstract: Under a hybrid theoretical perspective involving positive psychology (PosPsy) and ecological paradigm, this research attempts to explore the interrelationship between classroom environment and willingness to communicate (WTC) in English among EFL (English as a foreign language) learners in the normal universities in Shandong province, China. A survey method is used engaging a questionnaire comprised of demographic information and items on classroom environment and L2 WTC. The statistical analysis was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…To understand the relationships among various variables and willingness to communicate, MacIntyre et al (1998) proposed the most comprehensive willingness to communicate model, which identified two groups of variables, namely trait-like variables and situational context variables. The original model has been tested in several second language teaching contexts, for example, in China (Kun et al, 2020), Iran (Aliakbari et al, 2016), Japan (Aoyama & Takahashi, 2020), Pakistan (Bukhari et al, 2015), Poland (Mystkowska-Wiertelak, 2016), Taiwan (Lin, 2019), Thailand (Jongsermtrakoon & Vibulphol, 2010;Pattapong, 2015), and Turkey (Basöz & Erten, 2019). Recent development of the willingness to communicate model was influenced by the study of positive psychology which focused on positive internal and external variables such as emotion, grit, flow experience, and enjoyment (Dewaele & Dewaele, 2018;Dewaele & Pavelescu, 2021;Lee, 2020;Lee & Drajati, 2019;Lee & Hsieh, 2019;MacIntyre et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To understand the relationships among various variables and willingness to communicate, MacIntyre et al (1998) proposed the most comprehensive willingness to communicate model, which identified two groups of variables, namely trait-like variables and situational context variables. The original model has been tested in several second language teaching contexts, for example, in China (Kun et al, 2020), Iran (Aliakbari et al, 2016), Japan (Aoyama & Takahashi, 2020), Pakistan (Bukhari et al, 2015), Poland (Mystkowska-Wiertelak, 2016), Taiwan (Lin, 2019), Thailand (Jongsermtrakoon & Vibulphol, 2010;Pattapong, 2015), and Turkey (Basöz & Erten, 2019). Recent development of the willingness to communicate model was influenced by the study of positive psychology which focused on positive internal and external variables such as emotion, grit, flow experience, and enjoyment (Dewaele & Dewaele, 2018;Dewaele & Pavelescu, 2021;Lee, 2020;Lee & Drajati, 2019;Lee & Hsieh, 2019;MacIntyre et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Their heuristic WTC model identifies two groups of variables, namely trait-like variables and situational context variables (MacIntyre et al, 1998). Since then, the model has been tested in several second language teaching contexts including Iran (Alemi & Pahmforoosh, 2012), Thailand (Jongsermtrakoon & Vibulphol, 2010;Pattapong, 2015), Pakistan (Bukhari et al, 2015), Turkey (Basöz & Erten, 2019;Cetinkaya, 2005), Poland (Mystkowska-Wiertelak, 2016), Taiwan (Lin, 2019), and Japan (Aoyama & Takahashi, 2020), China (Kun et al, 2020). The findings from these studies suggested the dynamic relationship among the variables in different contexts.…”
Section: Introductionmentioning
confidence: 99%